Identification of G2607A mutation in EGFR gene with a significative rate in Moroccan patients with Bladder Cancer - El Hamdani, W.; Hadami, K.; Bensaid, M.; El Ahanidi, H.; Ameur, A.; Filali maltouf, A.; Abbar, M.; Attaleb, M.; Albouzidi, A.; El Mzibri, M. (Cellular and Molecular Biology, 2017)
The epidermal growth factor receptor (EGFR) is involved in the regulation of several cellular processes and in the development of many human cancers. Somatic mutations of EGFR at tyrosine kinase domain have been associated with clinical response to tyrosine kinase inhibitors (TKIs) in lung cancer patients. In this study, we evaluated the frequency of point mutations in EGFR for future use of TKI in clinical treatment of bladder cancer. A total, 50 Moroccan patient specimens with bladder cancer and 48 healthy controls were analysed for EGFR mutations in the region delimiting exons 18-21 by PCR amplification and direct sequencing. Our results showed the absence of mutations in the EGFR kinase domain in these exons in all analysed specimens. However, sequence analysis of the EGFR-TK domain, revealed the presence of (G2607A) polymorphism at exon 20. Statistical analysis showed significant difference in the frequencies of G2607A polymorphism between cancer cases and healthy controls (p=0.0001) and the frequencies of the GG and GA/AA genotypes among the cancer cases were 28% and 72%, respectively. Moreover, allelic frequencies of G2607A polymorphism showed significant difference between cancer cases and healthy controls (p=0.0025). Data analysis showed no significant association between G2607A polymorphism and patients' age, clinical stage and tumor grade (p > 0.05). However, a significant difference was found between this polymorphism and patients' sex that could be a sampling bias due to the very limited number of women with bladder cancer. Our findings highlight that, mutations in EGFR kinase domain is a rare event in bladder cancer, suggesting, that treatment of bladder cancer patients with TKI may not be effective. However, the EGFR G2607A polymorphism in exon 20 is frequent in bladder cancer cases and must be further explored for its relevance in the treatment of this disease.